Outcome of Hepatitis-E Virus Infection among Pregnant Women Admitted in a Tertiary Care Hospital - Tayyaba Wasim, Tayyaba Wasim; Javeria Mushtaq, Javeria Mushtaq; Waseem, Mustafa (Journal of Rawalpindi Medical College, 2022)
PURPOSE: To study the effect of post-operative Non-Steroidal Anti-inflammatory (NSAID) eye drops on macular thickness in patients without diabetic retinopathy measured by Optical Coherence Tomography (OCT) STUDY DESIGN: Quasi experimental study PLACE & DURATION OF STUDY: removed for blind review METHODOLOGY: Diabetic patients without retinopathy who required cataract surgery for visual rehabilitation were included in study. They were than divided into two groups. Group A included patients who received routine steroid+antibiotic post-operative drops while Group B comprised of patients who received nepafenac (0.1%) eye drops eight hourly in addition to routine post-operative eye drops. All patients underwent standard phacoemulsification and intraocular lens implantation followed by use of NSAID eye drops for a month. OCT measurements were done pre-operatively, 7 and 28 days post operatively. RESULTS: Comparison of central macular thickness between groups was significant at (Pre & 7 day post op) and insignificant at (7th day & 28th day post op) and (Pre & 28th day post op) i.e. 0.043, 0.834 and 0.084 respectively. However, difference of mean central macular thickness was significant at all follow-up periods i.e.0.003, 0.006, and 0.000 CONCLUSION: Post-operative NSAID in diabetic patients without retinopathy leads to a significant decrease in macular thickness as compared to controls after cataract surgery. KEY WORDS: Phacoemulsification, Optical Coherence Tomography, Non-steroidal Anti-Inflammatory Agents